Quand l’Université se saisit de la littérature d’enfance et de jeunesse - Isabelle Nières-Chevrel (Strenae)
Children's and young adult’s literature was introduced into French universities in the 1970s, and became a possible research subject in most of the humanities disciplines. Two questions arise with regard to the literary disciplines: does examining children’s and young adult literature, rather than "general literature" (for adults), lead to specific approaches and concepts? In these disciplines, which are more often focused on singular works than on literary series, does the simple fact of conducting research on a children’s picture book or novel necessarily bestow it with cultural legitimacy? And lastly, what might be the place and role of this varying research in the larger social field?